Exploratory study on the association of fish consumption with serum cotinine levels in the general adult population - Ning Zhu; Yusheng Li; Xiaoyan Jin; Mei Chen; Linfeng Wang; Chao Cao (BMC Nutrition)
Abstract Background This cross-sectional study examined the association between fish consumption and serum cotinine levels, a biomarker of tobacco exposure, among adults in the United States. Methods Data were obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between 2001 and 2018. A total of 32,766 participants were included after applying eligibility criteria. Fish consumption frequency was assessed via dietary questionnaires, and serum cotinine levels were measured using validated high-performance liquid chromatography–tandem mass spectrometry. Multiple linear regression and restricted cubic spline (RCS) models were used to evaluate the association between fish consumption and serum cotinine levels, adjusting for potential confounders. Results Higher fish consumption was significantly associated with lower serum cotinine levels across all models. Participants who consumed ≥ 6 fish meals per month had significantly lower serum cotinine levels compared to non-consumers (β = -0.20, 95% CI: -0.30 to -0.10; P < 0.001) after adjustment for confounding variables. RCS analysis revealed a non-linear relationship, with an inflection point at 4.53 meals per month (P for nonlinearity < 0.01). Stratified analyses by smoking status showed similar inverse associations among never smokers, former smokers, and current smokers, with no significant interaction observed (P for interaction = 0.218). Conclusion In this nationally representative sample of U.S. adults, higher fish consumption was independently associated with lower serum cotinine levels. These findings provide novel epidemiological evidence linking dietary habits to tobacco exposure biomarkers and suggest a potential role for fish consumption in supporting healthier lifestyle behaviors.